THE ANNIVERSARY COLLECTION “LICHT, MEHR LICHT!” – COMPENDIUM OF THE UNIVERSE - Polly Mukanova (Издател)
The anniversary collection “Licht, mehr Licht! in memory of Prof. Milen Kumanov: on the occasion of the 80th anniversary of the scientist’s birth” presents 168 works of various genres by 183 authors from 3 continents and 17 countries, arranged in semantic sections belonging to the bibliographic and historiographical series of Academic Publishing House “Za bukvite – O pismeneh” in the series “Faklonosci”, volume 32. The basis of e-libraries, published on the website of the Student Scientific Society of the University of Library Studies and Information Technologies (ULSIT), is described.